Targeted re-sequencing in malformations of cortical development: genotype-phenotype correlations. (August 2020) - Accogli, Andrea; Severino, Mariasavina; Riva, Antonella; Madia, Francesca; Balagura, Ganna; Iacomino, Michele; Carlini, Barbara; Baldassari, Simona; Giacomini, Thea; Croci, Carolina; Pisciotta, Livia; Messana, Tullio; et al.
Highlights: NGS panel identified genetic causes in one-fourth of our cohort (21.4 %). Positive genetic findings were more frequent in diffuse, bilateral MCD. Presence of other CNS anomalies was associated with positive genetic results. Specific MCD patterns may benefit of NGS panel approach as first diagnostic tier. Abstract: Purpose: Malformations of cortical development (MCD) are a phenotypically and genetically heterogeneous group of disorders, for which the diagnostic rate of genetic testing in a clinical setting remains to be clarified. In this study we aimed to assess the diagnostic rate of germline and pathogenic variants using a custom panel in a heterogeneous group of subjects with MCD and explore genotype-phenotype correlations. Methods: A total of 84 subjects with different MCD were enrolled. Genomic DNA was isolated from peripheral blood. Fifty-nine tartget genes were assessed using a custom next-generation sequencing (NGS) panel. Results: Genetic causes were identified in one-fourth of our cohort (21.4 %). Overall, we identified 19 pathogenic or likely pathogenic single-nucleotide variants in 11 genes among 18 subjects, including PAFAH1B1 (LIS1) (n = 3), TUBA1A (n = 3), DYNC1H1 (n = 3), ACTG1 (n = 2), TUBB2B (n = 1), TUBB3 (n = 1), DCX (n = 1), FLNA (n = 1), LAMA2 (n = 1), POMGNT2 (n = 1) and VLDLR (n = 1). The diagnostic yield was higher in patients with lissencephaly/pachygyria (60 %) (p = 0.001), cobblestone malformation (50 %), and subcortical band heterotopia (SBH) (40 %). Furthermore, five out of six subjects with suspect tubulinopathies on imaging harboured pathogenic variants in tubulin genes. Overall, germline pathogenic variants were more likely to be identified if MCD were diffuse (p = 0.002) and associated with other central nervous system malformations (p = 0.029). Moderate to severe intellectual disability was also more commonly associated with pathogenic variants (p = 0.044). Conclusion: Customized gene panels may support the diagnostic work-up for some specific MCD, especially when these are diffuse, bilateral and associated with other brain malformations.